Analysis of Student’s Creative Thinking Ability on Colloid Material - Siti Arma; Supriadi Supriadi (Jurnal Akademika Kimia, 2022)
This study aimed to describe students' creative thinking skills in Colloid material in class XI SMA Negeri 7 Palu. The type of this research was descriptive quantitative. The research sample consisted of 30 students. The data collected were in the form of test results for the ability to think creatively, which were obtained through giving essay questions as many as five items that expert validators had validated. The results of every item were on average 74.4% of fluency, while flexibility, elaboration, and originality, respectively, were 75.83%, 53.76%, 61.66%, and 47.5%. Based on the analysis of the four indicators above, it can be found that the students' creative thinking ability on colloid material in class XI SMA Negeri 7 Palu was in the medium category. Students need to be accustomed to working on questions that can require them to think creatively during learning to develop their ability in creative thinking and connect theory with everyday life.